Mestre Amaro, um lobisomem do canavial: a representação da licantropia em Fogo Morto - Müller, Dangelo (My University, 2014)
This work discusses the presence of the myth of the werewolf in the book Fogo Morto, by José Lins do Rego. They are approached the aspects of myth, social imaginary and identity presents in story, well as the form as those interact. The study focuses the character José Amaro, saddler of a rural locality of the Várzea do Paraíba, that through social imaginary haves your identity linked to archtype of the lycanthrope. The study is divided in four distinct moments: apresentation of the book Fogo Morto and his context in the brazilian literature; the composition of the myth of the werewolf in Fogo Morto; the development of a social imaginary and his effects in the community; the problem of the identity of the José Amaro.
Este trabalho discute a presença do mito do lobisomem na obra Fogo Morto, de José Lins do Rego. São abordados os aspectos do mito, do imaginário social e da identidade presentes no enredo, bem como a forma como esses interagem. O estudo centra-se no personagem José Amaro, seleiro de uma localidade rural da Várzea do Paraíba, que através do imaginário social tem sua identidade vinculada ao arquétipo do licantropo. O estudo divide-se em quatro momentos distintos: apresentação da obra Fogo Morto e sua contextualização na literatura brasileira; a constituição do mito do lobisomem em Fogo Morto; o desenvolvimento de um imaginário social e seus efeitos na comunidade; o problema da identidade de José Amaro.
Keywords: LITERATURA BRASILEIRA; José Lins do Rego, 1901-1957; Fogo morto (Obra literária); Animais mitológicos; Lobisomens; Imaginário social; Identidade cultural; Identidade social; Literatura brasileira; Crítica; Mythological animals; Werewolves; Social imaginary; Cultural identity; Group identity; Brazilian literature; Criticism